1999
DOI: 10.1111/j.1745-4549.1999.tb00395.x
|View full text |Cite
|
Sign up to set email alerts
|

ASCORBIC ACID DEGRADATION KINETICS DURING CONVENTIONAL and OHMIC HIEATING

Abstract: Ascorbic acid (vitamin C) degradation during electrical and conventional heating was studied to determine if the presence of an electric field altered the rate of degradation. Experiments were peiformed using a static ohmic heating apparatus, and heating histories were matched using applied voltage in the electrical case and hot oil in the conventional case. A statistical analysis showed that electric field has no significant effect on ascorbic acid degradation. Pseudo first order degradation kinetics were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 12 publications
7
34
0
Order By: Relevance
“…H 2 or O 2 gas). Lima, Heskitt, Burianek, Nokes, and Sastry (1999) and Assiry, Sastry, and Samaranayake (2003) concluded that electrolytic reactions were not evident with specially coated electrodes or in the use of high frequency power. zFurthermore, Castro et al (2004) explained that in an un-pressurized heater, if air is occluded in the sample, the air bubbles will expand with temperature, with the pressure remaining constant.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 or O 2 gas). Lima, Heskitt, Burianek, Nokes, and Sastry (1999) and Assiry, Sastry, and Samaranayake (2003) concluded that electrolytic reactions were not evident with specially coated electrodes or in the use of high frequency power. zFurthermore, Castro et al (2004) explained that in an un-pressurized heater, if air is occluded in the sample, the air bubbles will expand with temperature, with the pressure remaining constant.…”
Section: Resultsmentioning
confidence: 99%
“…With reference to kinetics of destruction of vitamin C in food systems, different buffer systems and real products with different processing methods have been examined (Frias, Oliveira, Cunha, & Oliveira, 1998;Hussein et al, 2000;Lathrop & Leung, 1980;Lee & Nagy, 1988;Lima, 1997;Lima, Heskitt, Burianek, Nokes, & Sastry, 1999;Rao, Lee, Katz, & Cooley, 1981;Robertson & Samaniego, 1986;van den Broeck, Ludikhuyze, Weemaes, Loey, & Hendrickx, 1998). Many of these studies are related to the storage of pasteurized juices or higher temperatures of processing.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between browning, oxygen content and Lascorbic acid has been discussed by other researchers (Lee & Nagy, 1988;Lima, Heskitt, Burianek, Nokes, & Sastry, 1999). Increasing the levels of dissolved oxygen in the juice by electrolysis caused a substantial increase in the development of browning reactions, due to the additional incorporation of dissolved oxygen in the juice.…”
Section: Controlmentioning
confidence: 84%